Effect of high-quality nursing on neurological function psychological moods quality of life of elderly patients with stroke - Gao, Na; Li, Yaqiang; Sang, Changru; He, Jiale; Chen, Congxia (Frontiers in Neurology, 2023)
Objectives The primary objective of the present investigation was to meticulously examine the efficacy of high-quality nursing care (HQN) on neurological restoration, amelioration of adverse psychological states, and augmentation of quality of life in geriatric patients diagnosed with acute cerebral infarction (ACI). Methods A cohort of 240 patients, afflicted by ACI and admitted to our healthcare institution between February 2020 and March 2023, were incorporated into this longitudinal prospective analysis. Employing a random number table methodology, the patient cohort was bifurcated into a control group (n = 120) receiving conventional care and an observation group (n = 120) receiving HQN. Comparisons were conducted between the two cohorts concerning neurological functionality [as quantified by the National Institutes of Health Stroke Scales (NIHSS) and Barthel Index (BI) scores], psychological wellbeing [utilizing the Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) scores], overall quality of life [assessed via the Generic Quality of Life Inventory-74 (GQOLI-74) scores], and self-perceived burden [evaluated through the Self-Perceived Burden Scale (SPBS)]. Further assessments included patient satisfaction and incidence of complications, both in the pre- and post-interventional phases. Results Post-intervention, the observation group demonstrated superior outcomes compared to the control group, as evidenced by diminished NIHSS and SPBS scores and elevated BI metrics. Moreover, SAS and SDS scores in both groups manifested a decline post-intervention; however, the decrement was statistically more pronounced in the observation group (P < 0.05). Similarly, all dimensions of GQOLI-74 showed an upward trend in both cohorts, yet the increase was significantly more substantial in the observation group (P < 0.05). Furthermore, the observation group exhibited a reduced frequency of complications coupled with heightened levels of nursing satisfaction. Conclusion The implementation of HQN in the geriatric population afflicted by ACI markedly enhances neurological recuperation, attenuates adverse psychological states, and ameliorates overall quality of life. The intervention is also associated with a diminution in complication rates and an increase in nursing satisfaction, thereby substantiating its clinical utility.